2010
DOI: 10.1038/onc.2009.495
|View full text |Cite
|
Sign up to set email alerts
|

Plakoglobin interacts with and increases the protein levels of metastasis suppressor Nm23-H2 and regulates the expression of Nm23-H1

Abstract: Plakoglobin (c-catenin) is a homolog of b-catenin with similar dual adhesive and signaling functions. The adhesive function of these proteins is mediated by their interactions with cadherins, whereas their signaling activity is regulated by association with various intracellular partners. In this respect, b-catenin has a well-defined oncogenic activity through its role in the Wnt signaling pathway, whereas plakoglobin acts as a tumor/metastasis suppressor through mechanisms that remain unclear. We previously e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 68 publications
2
57
0
Order By: Relevance
“…ATP is required for phosphorylation of MLC by MLCK, and we therefore explored the possible role of Nm23, a member of the nucleoside diphosphate kinase (NDPK) family, which was recently identified as a partner of c-catenin in tumor cells (Aktary et al, 2010). Nm23 could be found at endothelial junctions together with EMMPRIN and c-catenin, and knockdown of either of these proteins resulted in a significant decrease in Nm23 localization to these sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATP is required for phosphorylation of MLC by MLCK, and we therefore explored the possible role of Nm23, a member of the nucleoside diphosphate kinase (NDPK) family, which was recently identified as a partner of c-catenin in tumor cells (Aktary et al, 2010). Nm23 could be found at endothelial junctions together with EMMPRIN and c-catenin, and knockdown of either of these proteins resulted in a significant decrease in Nm23 localization to these sites.…”
Section: Discussionmentioning
confidence: 99%
“…An EMMPRIN-c-catenin-Nm23 complex regulates actomyosin contractility at endothelial cell junctions through local ATP production Given that actomyosin contractility requires ATP, we next investigated the possible role at the junction of the reported ccatenin partner nucleoside diphosphate kinase Nm23 (Aktary et al, 2010), which is able to generate ATP by exchanging phosphate groups from NTP to ADP. The presence of Nm23 in the EMMPRIN molecular complex was confirmed by coimmunoprecipitation from endothelial cell lysates (Fig.…”
Section: Emmprin Associates With C-catenin At Endothelial Junctionsmentioning
confidence: 99%
“…PG is also found in the cytoplasm and nucleus (Green and Simpson, 2007;Schmidt and Koch, 2007), where it is able to act independently of its function in intercellular adhesion. Its adhesionindependent functions are still not well defined, but the data suggest that PG can regulate gene expression and protein stability (Aktary et al, 2010;Hakimelahi et al, 2000;Shimizu et al, 2008) in both a -catenin-dependent and -independent manner (Raurell et al, 2006;Teuliere et al, 2004;Yin and Green, 2004;Zhurinsky et al, 2000).…”
Section: Abstract: Armadillo Protein Desmosome Extracellular Matrimentioning
confidence: 99%
“…PG is also found in the cytoplasm and nucleus (Green and Simpson, 2007;Schmidt and Koch, 2007), where it is able to act independently of its function in intercellular adhesion. Its adhesionindependent functions are still not well defined, but the data suggest that PG can regulate gene expression and protein stability (Aktary et al, 2010;Hakimelahi et al, 2000;Shimizu et al, 2008) in both a -catenin-dependent and -independent manner (Raurell et al, 2006;Teuliere et al, 2004;Yin and Green, 2004;Zhurinsky et al, 2000).Recently we demonstrated that PG not only inhibits motility of keratinocytes in contact, but also inhibits Src-dependent single cell motility (Yin et al, 2005b). The observed changes in motility and altered cell morphology of PG -/-keratinocytes suggested to us that PG could be regulating cell-substrate interactions by modulating components of the extracellular matrix (ECM), its integrin receptors and/or the molecules involved in ECM-triggered motility cues.…”
mentioning
confidence: 99%
“…46,47 Accumulating evidence suggests that cytosolic NME/NDPKs NME1 but also often NME2, interact with and affect different components and regulators of the cytoskeleton, including actin-binding proteins, intermediate filaments, and cytoskeleton attachment structures (adherens junctions, desmosomes, and focal adhesions) in cells from a variety of organisms and tissues, and in the course of development, suggesting that this association is evolutionarily conserved and may serve an essential function. [48][49][50][51][52][53][54][55] The interactions of NDPK with components of the cytoskeletal machinery are highly relevant, given the well-established role of the cytoskeleton in cell motility, a critical determinant of the metastasis process. NME1 has also been reported to bind proteins belonging to small and heterotrimeric G-proteins ( [56][57][58][59][60][61] ; and Filic 62 upcoming issue; Abu-Taha et al, 63 this issue), transcriptional complexes ( 64-69 ; Sharma et al, 70 Pandey and Robertson, 71 and Puts et al, 72 all in this issue), and components of signaling pathways of MAPK, [73][74][75] TGF-β [76][77][78] and Notch, 79 as well as other factors promoting invasion and metastasis ( 80,81 ; Ferrucci et al 82 upcoming issue).…”
Section: Nme In Metastasismentioning
confidence: 99%